PENGARUH PERSENTASE SAHAM DITAWARKAN, PROFITABILITAS, DAN EARNING PER SHARE TERHADAP UNDERPRICING PADA PERUSAHAAN IPO DI BURSA EFEK INDONESIA TAHUN 2017-2018 - I Kadek Gillang Nugraha Rianttara; I Gusti Agung Krisna Lestari (Universitas Triatma Mulya, 2020)
Various ways can be done by a company in fulfilling capital needs to make the company grow, one of the ways to do is to sell shares to the public which is usually often called by conducting an IPO (initial public offering). Generally, when this offer is made, there is often an underpricing phenomenon, underpricing is there a situation when the initial stock price is lower than when the stock price is currently on the secondary market. This study aims to determine the effect of the percentage of shares offered, profitability, and earnings per share on underpricing of IPO companies on the Indonesia Stock Exchange in 2017-2018. The population in this study are listed companies doing an IPO in the 2017-2018 period on the Indonesia Stock Exchange (IDX). The method used in this research is purposive sampling by collecting a total sample of 61 companies. The data used in this study are secondary data obtained from the company's prospectus. The results of this study indicate that the percentage of shares offered has a positive effect on underpricing, profitability has no effect on underpricing, and earnings per share has a negative effect on underpricing. The results of the coefficient of determination (Adjusted R Square) of 0.290, this shows that the contribution of the influence of the independent variable, namely the percentage of shares offered, profitability, and earnings per share is 29% and the remaining 71% is influenced by other factors not examined in the study this.